A review on nanopesticides for plant protection synthesized using the supramolecular chemistry of layered hydroxide hosts - Mohd Zobir, Syazwan Afif; Ali, Asgar; Adzmi, Fariz; Sulaiman, Mohd Roslan; Ahmad, Khairulmazmi (Multidisciplinary Digital Publishing Institute, 2021)
The rapid growth in the human population has triggered increased demand for food supply, and in turn has prompted a higher amount of agrochemical usage to meet the gaps between food production and consumption. The problem with conventional agro-nanochemicals is the reduced effectiveness of the active ingredient in reaching the target, along with leaching, evaporation, etc., which ultimately affect the environment and life, including humans. Fortunately, nanotechnology platforms offer a new life for conventional pesticides, which improves bioavailability through different kinetics, mechanisms and pathways on their target organisms, thus enabling them to suitably bypass biological and other unwanted resistances and therefore increase their efficacy. This review is intended to serve the scientific community for research, development and innovation (RDI) purposes, by providing an overview on the current status of the host–guest supramolecular chemistry of nanopesticides, focusing on only the two-dimensional (2D), brucite-like inorganic layered hydroxides, layered hydroxide salts and layered double hydroxides as the functional nanocarriers or as the hosts in smart nanodelivery systems of pesticides for plant protection. Zinc layered hydroxides and zinc/aluminum-layered double hydroxides were found to be the most popular choices of hosts, presumably due to their relative ease to prepare and cheap cost. Other hosts including Mg/Al-, Co/Cr-, Mg/Fe-, Mg/Al/Fe-, Zn/Cr- and Zn/Cu-LDHs were also used. This review also covers various pesticides which were used as the guest active agents using supramolecular host–guest chemistry to combat various pests for plant protection. This looks towards a new generation of agrochemicals, “agro-nanochemicals”, which are more effective, and friendly to life, humans and the environment.